2017
DOI: 10.1080/10872981.2017.1336418
|View full text |Cite
|
Sign up to set email alerts
|

Successful adaptation of a research methods course in South America

Abstract: Background: South America has low research productivity. The lack of a structured research curriculum is one of the barriers to conducting research.Objective: To report our experience adapting an active learning-based research methods curriculum to improve research productivity at a university in Ecuador.Design: We used a mixed-method approach to test the adaptation of the research curriculum at Universidad Catolica Santiago de Guayaquil. The curriculum uses a flipped classroom and active learning approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…It is a common problem for many medical faculties, especially those in developing countries, to provide students with opportunities for research experience during pre-graduate medical education and to convince faculty members to become mentors [6,9,11,19,34,36,[40][41][42]. Our ndings have revealed that the novel idea of performing research with students coupled with the intensity of daily routine workload limits the number of volunteers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is a common problem for many medical faculties, especially those in developing countries, to provide students with opportunities for research experience during pre-graduate medical education and to convince faculty members to become mentors [6,9,11,19,34,36,[40][41][42]. Our ndings have revealed that the novel idea of performing research with students coupled with the intensity of daily routine workload limits the number of volunteers.…”
Section: Discussionmentioning
confidence: 90%
“…Recommendations put forward in this study in order to increase the number of mentors included explaining the advantages of working with students to the faculty members; introducing factors that encourage mentoring such as academic promotion criteria; and assigning non-medical faculty members as advisors. In consequence, as suggested by Tamariza et al [41], universities wishing to support student research need to create a pool of mentors.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common problem for many medical faculties, especially those in developing countries, to provide students with opportunities for research experience during pre-graduate medical education and to convince faculty members to become mentors [6,9,11,19,40,42,[46][47][48]. Our ndings have revealed that the novel idea of performing research with students coupled with the intensity of daily routine workload limits the number of volunteers.…”
Section: Discussionmentioning
confidence: 90%
“…A majority of educational programs was mandatory (N = 16). Three publications presented elective summer schools developed for students with interest in research and scientific projects (16,29,30) Timing of educational interventions was most often between 1st and 3rd study year. In three of the identified curricular interventions teaching of science is spread across more than three study years, as for example in the full study program on EbM described by Marusic (28).…”
Section: Resultsmentioning
confidence: 99%
“…knowledge, measures of scientific competence based on tested instruments and randomized trials testing different standards of educational interventions (see for example31,32). Results were quite heterogeneous: some studies showed improvement in student competencies regarding basic principles of science (see for example29,30,33,34), some were able to identify higher competencies…”
mentioning
confidence: 99%